Production and Evaluation of Natural Sweeteners and Packaging Materials on Peach compote's shelf life - Manal, A. El-Gendy; Sanaa, S.H. Aly (Food Technology Research Journal)
Peach compote is one of the products that preserve peach fruits from deterioration until consumption. It plays an important role in human nutrition, so this study aims to preserve peach slices by using natural sweeteners such as sucrose, High Fructose Corn Syrup (H.F.C.S), and stevia. The study also examined the effects of packaging in glass and plastic jars on preserving quality and extending the shelf life of peach compote. The samples were stored for 3 months at 4±2°C. The study found that the TSS, titratable acidity, and reducing sugars increased, while the pH, ascorbic acid, non-reducing sugars, and color decreased. The microbiological evaluation showed that all treatments had the lowest microbial load throughout the storage period and were free from mold and yeasts. The sensory evaluation showed that treatments T6 (H.F.C.S + stevia) and T5 (sucrose + stevia) were the best throughout the storage life when packaged in glass jars